An analysis of research published in the International Journal of Managing Projects in Business from 2008 to 2019. Issue 3 (3rd March 2022) - Ayat, Muhammad; Malikah,; Ullah, Azmat; Kang, Changwook
Abstract : Purpose: This study examines scholarly communications in the International Journal of Managing Projects in Business (IJMPB) and identifies the journal's leading trends from 2008 to 2019. Design/methodology/approach: This study analyzed a sample of 522 articles published in the IJMPB since its inception in 2008 until 2019. A set of bibliometric measures was used in the study to identify publication trends, citation structures, leading authors, institutions and countries. Additionally, analysis of research methodologies, industrial sectors and research themes of the articles was carried out through a rigorous content analysis. To examine the changes in journal expansion over time, the duration of publications (from 2008 to 2019) was divided into three subperiods. Findings: The study findings show that 793 authors from 370 institutions and 58 countries contributed to the journal during this period. In terms of contributions, Australia and the Scandinavian countries are at the top, while Asian and African countries occupy a lower position. Moreover, among authors, Derek H.T. Walker was found to be the most prolific, with the highest weighting score and number of articles. Similarly, RMIT University of Australia emerged as the most productive institution. The articles were predominantly case studies followed by mixed methods (i.e. both surveys and interviews are used for data collection). Most of the articles in the sample were related to project management in general. However, several articles reported on construction, information technology (IT) and manufacturing projects. Practical implications: This study is useful for the researcher community to understand the journal's scientific productivity. Further, it will also help identify dominant topics in the field of project management. Originality/value: This is the first comprehensive review article presenting a general overview of the journal's leading trends and researchers since its inception in 2008.